Pengaruh E-Commerce, Kepribadian dan Ekspektasi Pendapatan Terhadap Minat Berwirausaha Ditinjau dalam Prespektif Ekonomi Islam: (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Ar-Raniry) - Eka Fitri; Khairul Amri; Azimah Dianah (Yayasan Kawanad, 2023)
The number of university graduates in Indonesia is increasing every year but it is not proportional to the number of available jobs so it has an impact on increasing educated unemployment. One of the efforts to reduce the unemployment rate among the educated is by cultivating an entrepreneurial spirit in students. This study aims to determine the effect of e-commerce, personality, and income expectations on FEBI students' entrepreneurial interests partially or simultaneously. The data analysis technique in this study was multiple linear regression analysis by distributing questionnaires to 91 respondents. The results of this study state that e-commerce, personality, and income expectations have a positive and significant effect on FEBI students' entrepreneurial interests. Simultaneously or together with e-commerce, personality, and income expectations have a positive and significant effect on FEBI student entrepreneurship interest.